FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA EARNINGS MANAGEMENT PADA PERUSAHAAN DI INDONESIA - Ita Trisnawati; Dinda Aulia Lestiawati (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to obtain empirical evidence regarding the effect of leverage, firm size, tax planning, managerial ownership, institutional ownership, profitability, and independent commissioners as independent variables. And earnings management variable as the dependent variable. This study uses 126 data from 42 manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 to 2020 and the research sample uses the purpose sampling method. This study uses multiple regression methods and hypothesis testing. the results of this study indicate that leverage, institutional ownership, and profitability have a positive effect on earnings management, while independent commissioners have a negative effect on earnings management. On the other hand, firm size, tax planning, and managerial ownership have no effect on earnings management.